Economic optimization and dynamic control of pressure‐swing distillation for separating the ternary azeotrope of butanone/n‐heptane/isopropanol. Issue 9 (27th May 2022) - Ma, Cuncheng; Sun, Defeng; Zhang, Fangkun; Xu, Qilei; Zhu, Zhaoyou; Wang, Yinglong; Shan, Baoming
Abstract: BACKGROUND: Economic optimization and dynamic control of the separation process for recovering the ternary mixture of butanone (MEK)/ n ‐heptane/isopropanol (IPA) from industrial wastewater is a significant topic. In this work, the optimal pressure‐swing distillation (PSD) sequence, heat integration and dynamic control for separating MEK/ n ‐heptane/IPA were investigated systematically. The optimal separation sequence was determined by combining the minimum total annual cost (TAC) with the residual curves map (RCM). Pressure‐swing distillation with non‐heat integration, partial heat integration or full heat integration was compared in terms of TAC. Dynamic control schemes were designed for optimal processes of two separation sequences with and without heat integration. RESULTS: The results demonstrate that the TAC of optimal PSD with non‐heat integration process can be reduced by 31.11%, whereas the TAC of optimal partial heat integration and full heat integration schemes can be reduced by 39.73% and 40.96%, respectively. The dynamic performance of all control schemes that can resist ±20% feed flow disturbances and composition disturbances are compared with the integral of squared error. CONCLUSION: It is demonstrated that PSD with full integration process (FHIPSD) for separating MEK/ n‐ heptane/IPA has optimal economic performance, whereas PSD with non‐heat integration process (NTIPSD) has the optimal dynamic performance and robust stability. This work provides a significant reference for industrial separation of MEK/ n ‐heptane/IPA. © 2022 Society of Chemical Industry (SCI).